Abnormal Vacuole Membrane Protein-1 Expression in Parkinson’s Disease Patients - Al-Nusaif, Murad; Cheng, Cheng; Li, Tianbai; Jia, Congcong; Wang, Panpan; Li, Song; Le, Weidong (Frontiers in Neuroscience, 2022)
Abstract Background Parkinson's disease (PD) is pathologically characterized by progressive dopaminergic (DAergic) neuron loss in the substantia nigra pars compacta (SNpc) and accumulation of intracytoplasmic α-synuclein-containing Lewy bodies. Autophagy has been identified as a critical component in the development and progression of PD. Several autophagy genes have been identified as being altered in PD. One of those genes, vacuole membrane protein-1 (VMP1), an autophagy protein localized in the endoplasmic reticulum (ER) in DAergic neurons, has been shown to cause motor disorder, severe loss of DAergic neurons, and autophagy flux disturbance in the VMP1 knockout mouse model. Objective: To evaluate for the first time the alteration on the expression of the VMP1 gene and its clinical correlations in peripheral blood mononuclear cells (PBMCs) of a relatively large sample of PD patients. Methods: We assessed the VMP1 mRNA levels in PD patients (n = 229) and healthy controls (HC) (n = 209) using real-time quantitative PCR (RT-qPCR), and the VMP1 protein levels in PD patients (n = 27) and HC (n = 27) using Western blot (WB). Then, we analyzed the VMP1 expression levels and clinical features of PD patients. Results: Our findings revealed that VMP1 levels in the PD group were significantly lower than in the HC group (RT-qPCR p<0.01 and WB p<0.001). The VMP1 expression was significantly lower as the disease progressed, which could be ameliorated by administering DAergic receptor agonists. Moreover, Receiver Operating Characteristic Curve (ROC) curve analysis showed that VMP1 mRNA and protein level AUCs were 64.5 %, p<0.01, and 83.4 %, p<0.01, respectively. Conclusions: This case-control study demonstrates that peripheral VMP1 level altered in PD patients and may serve as a potential endogenous diagnostic marker of PD.